Modern technologies and mobile apps in developing speaking skill - Eshankulovna, Rustamova Adash (Linguistics and Culture Review, 2021)
Speaking is one of the abilities that students must develop when studying English. Speaking is a necessary technique for communication. Improving pupils’ speaking ability has long been a priority in the classroom. Various novel technologies are being developed to educate speaking skills in classrooms in the rapidly expanding twenty-first century. Technology is the means through which we may gain access to this updated environment. Technology has been viewed as a means of assisting pupils in improving language abilities such as speaking ability. The Internet, podcasts, video conferencing, movies, and voice recognition software are regarded as the most effective instruments for training public speaking. The purpose of this paper is to explore some of the current tools that are accessible to English instructors today to help second or foreign language learners improve their speaking skills.